Rekonstruowanie żydowskiego miasta. Nils Roemer: German City, Jewish Memory. The Story of Worms. Waltham, Brandeis University Press, 2010, pp. 316. Michael Meng: Shattered Spaces. Encountering Jewish Ruins in Postwar Germany and Poland - Wolski, Paweł (Narracje o Zagładzie [czasopismo zamknięte], 2015)
Reconstructing a Jewish town. Nils Roemer: German City, Jewish Memory. The Story of Worms. Waltham, Brandeis University Press, 2010, pp. 316. Michael Meng: Shattered Spaces. Encountering Jewish Ruins in Postwar Germany and Poland. Cambridge, Harvard University Press, 2011, pp. 351. The text briefly compares two books: Nils Roemer’s German City, Jewish Memory. The Story of Worms and Michael Meng’s Shattered Spaces. Encountering Jewish Ruins in Postwar Germany and Poland. Both represent fascinating approaches to the process of the reconstruction of the Jewish identity as an important part of the European urban culture destroyed during WWII. By discussing these issues on the examples of Worms (Roemer) and Warsaw, Wrocław, Potsdam, Berlin (Meng) both, albeit in different ways, restore the Jewish identity of these cities not only by approaching the history of historical or architectural landmarks, but also by discussing some less material, discoursive memory markers such as mythology, tourism, politics etc.